EXPLORING NOVEL MOLECULAR MECHANISMS OF HELQ IN DNA DAMAGE REPAIR - Pan, Jin Ke Michele (2024)
Correct genomic duplication and its maintenance during cellular processes is key to survival, and any disruptions to these processes can lead to the development of pathologies such as cancers, neurodevelopmental issues, and infertility. Cells have evolved a plethora of mechanisms to deal with threats to the genome, which all fall under the category of DNA damage repair (DDR). Key enzymes in these processes are helicases/translocases, which are proteins capable of harnessing ATP hydrolysis and utilise it to translocate and remodel DNA and RNA molecules. HelQ is a ssDNA-dependent helicase with a 3’ to 5’ directionality, which was originally described to be involved in repair of intrastrand crosslinks (ICLs). We showed that this helicase has strong sequence homology to Ski2 RNA helicases and discovered a novel role of this helicase in the resolution of R-loops (DNA:RNA hydrids with a displaced ssDNA). Furthermore, we elucidated the molecular mechanism behind this process by identifying a key protein interactant, the exoribonuclease XRN2 that is involved in degrading the RNA molecule once freed from the DNA template. Lastly, we attempted to further investigate the role of HelQ in homology mediated repair and more specifically Break Induced Repair (BIR), via a cell-based reporter system. Unfortunately, the reporter plasmid did not work as expected but these initial efforts represent a vital attempt in advancing our understanding of HelQ’s role in DDR.